Metal Valence State Modulation Strategy to Design Core@shell Hollow Carbon Microspheres@MoSe2/MoOx Multicomponent Composites for Anti‐Corrosion and Microwave Absorption - Xiao, Junxiong; Zhan, Beibei; Qi, Xiaosi; Ding, Junfei; Qu, Yunpeng; Gong, Xiu; Yang, Jing‐Liang; Wang, Lei; Zhong, Wei; Che, Renchao (Small (Weinheim an der Bergstrasse, Germany), 2025)
The exploitation of multicomponent composites (MCCs) has become the main pathway for obtaining advanced microwave absorption materials (MAMs). Herein, a metal valence state modulation strategy is proposed to tune the electromagnetic (EM) parameters and improve microwave absorption performances. Core@shell hollow carbon microspheres@MoSe2 and hollow carbon microspheres@MoSe2/MoOx MCCs with various mixed‐valence states content are well‐designed and produced by a simple hydrothermal reaction or/and heat treatment process. The results reveal that the thermal treatment of hollow carbon microspheres@MoSe2 in Ar and Ar/H2 leads to the in situ formation of MoOx and multivalence state, respectively, and the enhanced content of Mo4+ in the designed MCCs greatly boosts their impedance matching characteristics, polarization, and conduction loss capacities, which lead to their evidently improved EM wave absorption properties. Amongst, the as‐prepared hollow carbon microspheres@MoSe2/MoOx MCCs achieve an effective absorption bandwidth of 5.80 GHz under a matching thickness of 1.97 mm and minimum reflection loss of −21.49 dB. Therefore, this work offers a simple and universal method to fabricate core@shell hollow carbon microspheres@MoSe2/MoOx MCCs, and a novel and feasible metal valence state modulation strategy is proposed to develop high‐efficiency MAMs. Metal valence state modulation strategy is adopted to design core@shell structured hollow carbon spheres@MoSe2/MoOx multicomponent nanocomposites for their boosted impedance matching characteristics, conduction and polarization loss abilities, and comprehensive microwave absorption properties.